The Roy's adaptation model in a patient with Guillain-Barre Syndrome (GBS): A case report - Fithriyyah, Yayu; Haryani, Haryani (BKM Public Health and Community Medicine, 2021)
ABSTRACT Background: Guillain-barré syndrome (GBS) incidence may increase during an infectious disease outbreak or pandemic. Disease progression often has an impact on the patient and family. Objective: presents how Roy Adaptation Model (RAM) can guide nurses to assist and identify patient needs with GBS in a hospital setting. Method: A case report. The RAM assessment uses Russo (2019) through interviews and observation, and the RAM intervention guided by Akram et al. (2019). Results: Patients showed adaptive behavior following RAM intervention in 4 modes. RAM intervention by integrating patient and family to help the patient's cognators coping with recognizing and responding adaptive self-management to stimuli. Conclusion: The RAM guidelines were applicable for nurses to identify realistic and effective interventions for patients diagnosed with GBS involving the family in the hospital setting. Keywords: guillain-barré syndrome; nursing; roy adaptation model; intervention roy adaptation model.